AGILE METHODS IMPLEMENTATION E-COMMERCE WEB BASE BUMDES SINAR PETIR SOLUSI PENGOPTIMALAN SUMBER DAYA ALAM DAN EKONOMI DESA - Muhammad Syidqi Al Badwi; Muhammad Syahrul Gunawan; Afid Nuryadi; Wasis Haryono (Journal of Research and Publication Innovation, 2025)
This research focuses on developing a web-based e-commerce application to support the Village- Owned Enterprises (BUMDes) in Sinar Petir Village, Talang Padang, Tanggamus, Lampung. The primary objective of this application is to expand the marketing reach of products and simplify operations through the adoption of e-commerce technology. Currently, BUMDes conducts its sales activities traditionally, which limits marketing potential and relies on manual record-keeping systems. The research employs the Agile method, enabling iterative and flexible application development tailored to user feedback. Data collection techniques include interviews, field observations, and literature reviews to understand user needs and challenges. The developed application features product management, customer registration, payment processing, and detailed reporting to create a user-friendly experience for both administrators and customers. The implementation of this platform is expected to drive economic growth in the village by expanding market reach and enhancing operational efficiency. Furthermore, it has the potential to generate new job opportunities and increase the visibility of local products in the global market. Future development plans include adding features such as real-time customer support and integration with social media marketing tools.